From Knowledge to Wealth : Transforming Russian Science and Technology for a Modern Knowledge Economy - Watkins, Alfred (World Bank, Washington, DC, 2014)
Russia possesses a sophisticated science and technology (S&T) infrastructure (research capability, technically trained workforce, and technical research universities) which, even today, is a world leader in many fields. Despite this world class basic research capacity, Russia's exports are primarily raw materials. At a time when wealth depends to an increasing degree on knowledge, Russia does not have an effective system for converting its scientific capacity into wealth. Russia's S&T resources are isolated bureaucratically (they are deployed in the rigid hierarchical system devised in the 1920s to mobilize resources for rapid state-planned industrial development and national defense), functionally (there are few links between the supply of S&T output by research institutes and the demand for S&T by Russian or foreign enterprises), and geographically (many assets are located in formerly closed cities or isolated science/atomic cities). Overcoming these inefficiencies and adjusting the S&T system to the demands of a market economy will require a major program of institutional and sectoral reform. Part I of this paper describes the ambiguous legacy of the Soviet S&T system and the status of the Russian S&T sector after 10 years of transition. Part II describes the evolution of the Russian system of intellectual property rights protection from Soviet times to the present and argues that Russia will never develop a successful commercialization program until it clarifies the ownership of the large stock of intellectual property funded with federal budget resources. Part III outlines a comprehensive 10-point sectoral reform program to improve the efficiency of government research and development spending and link the Russian S&T system with market forces.